VILLAGE MINIMUM SERVICE STANDARDS IN BUATA VILLAGE, BOTUPINGGE SUB-DISTRICT, BONE BOLANGO DISTRICT - Ameliyati Hasyim; Karlina Napu; Harsono Ahmad (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This paper aims to find out and analyze the Village Minimum Service Standars in Buata Village, Botupingge District, Bone Bolango Regency. The approach used in this paper is qualitative. The data collection techniques used in this paper are observation, in-depth interviews, and documentation. The data analysis technique used in qualitative data analysis is inductive, which is a study based on the data obtained and then developed into a hypothesis. Based on the hypothesis formulated based on the data.The paper results show that administrative sevices in Buata Village have met the minimum service standars following the regulation of the Minister of Home Affairs number 2 of 2017 concerning minimum village service standars. Buata Village has followed these three crucial points` direction, laws, and rules. The Buata Village government`s implementation could have been more optimal,whether consciously or unconsciously. The Buata Village Government still finds several obstacles or factors, including the lack of maximum service to the community, inadequate facilities, ineffective human resources, and lack of pro-activity from the community.